Die Natur des Bewußtseins in Hegels Phänomenologie des Geistes - Gutberlet, L.C., Albert (Alpha Omega, 2019)
Summary: For Hegel, what moves human history is the dialectical nature of consciousness. The analysis of the Introduction to Hegel=s “Phenomenology of Spirit” shows that the dialectical nature of consciousness is ultimately rooted in its unconscious claim for absolute power over the world of experience. The dialectical process culminates in absolute knowledge as the reconciliation of all opposition. However, this “reconciliation” is only the self-awareness of the intrinsically contradictory nature of consciousness. Parole chiave: Coscienza, Sapere Assoluto, Dialettica, Natura, Contraddizione, Istinto di Potere. Keywords: Consciousness, Absolute Knowledge, Dialectics, Nature, Contradiction, Power-drive.